METODE PEMBELAJARAN AL-QUR’AN AN-NAHDLIYAH PADA KEGIATAN EKSTRAKURIKULER DALAM RANGKA MENINGKATKAN PERKEMBANGAN JIWA KEAGAMAAN ANAK - Nurul Hakim; Yusnia Naelin Na’imah (PREMIERE : Journal of Islamic Elementary Education, 2019)
One aspect of religious education that is not getting enough attention is Al-Qur'an reading education. In general, parents are more focused on general education so that many Muslim children cannot read and write the Qur'an. As a first step is to lay a strong religious foundation for the child as a preparation to navigate his life and life later. Based on these problems, the Qur'anic teachers must find solutions or solutions. One of them is to use interesting and understood methods so that children and parents are interested in learning and include their children in Al-Qur'an educational institutions. But as far as the authors know that there is still a need to improve the quality of the Al-Qur'an education. The formulation of the problem in this study includes three things, namely: 1. what is the method applied in the MI Salafiyah Bangilan Tuban ?, 2. what are the results of the method applied at the MI Salafiyah BangilanTuban? a child at MI Salafiyah Bangilan Tuban? This study aims to describe 1. Al-Qur'an learning methods applied at the MI Salafiyah Bangilan Bangilan Tuban, 2. describing the results of the application of methods in MI Salafiyah Bangilan Tuban, and 3. supporting and inhibiting factors in improving the development of children's religious spirit at MI Salafiyah Bangilan Tuban. Data was collected using the method of observation, interviews, documentation, and methods of data analysis obtained from the results of the research described in the form of analytical methods, qualitative descriptive. From the results of the analysis, it can be seen that the Al-Qur'an learning method in MI Salafiyah is supported by guidebooks, habituation, practice, memorization, and giving assignments, as well as playing and stories. The activity can run well. This can be seen from graduates who are able to read and write the Qur'an and apply it in daily life. The results of applying these methods include: 1. students can read the Qur'an properly and correctly based on the rules of recitation, 2. children can pray well and get used to living in Islamic nuances, 3. students can memorize letters -short letters relating to daily life and can write the Qur'an properly and correctly and 4. students can understand the basics of religion. While the supporting and inhibiting factors in the development of a child's religious soul. Supporting factors include: 1. the existence of adequate facilities and infrastructure, 2. the existence of togetherness between teachers, 3. the presence of santri enthusiasm, 4. the existence of supporting materials or materials, 5. the existence of extra activities. Inhibiting factors include: 1. lack of discipline both teachers and santri, 2. lack of attention and cooperation from some guardians of students, 3. time constraints, 4. limitations of teaching media, 5. lack of knowledge of child psychology, 6. limited funds.